2017
DOI: 10.1371/journal.pone.0174921
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the α1β2/α2β1 subunit interface contributes to the increased hemoglobin-oxygen affinity of high-altitude deer mice

Abstract: BackgroundDeer mice (Peromyscus maniculatus) that are native to high altitudes in the Rocky Mountains have evolved hemoglobins with an increased oxygen-binding affinity relative to those of lowland conspecifics. To elucidate the molecular mechanisms responsible for the evolved increase in hemoglobin-oxygen affinity, the crystal structure of the highland hemoglobin variant was solved and compared with the previously reported structure for the lowland variant.ResultsHighland hemoglobin yielded at least two cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Wild deer mice remain active throughout the year in the extreme HA habitat where they must overcome ambient hypoxia, cold temperatures, and food scarcity. They have evolved novel hemoglobin isoforms with increased O 2 binding affinity to surmount partially the low ambient O 2 availability (7,27,64); however, these isoforms are not always expressed and are insufficient to support the aerobic demands of deer mice fully, necessitating other strategies to increase O 2 uptake and delivery. Hammond et al (18) reported that deer mice that were raised and tested at LA exhibit higher aerobic capacity and basal metabolic rate than those that were either raised or acclimated as adults and tested at HA.…”
Section: Discussionmentioning
confidence: 99%
“…Wild deer mice remain active throughout the year in the extreme HA habitat where they must overcome ambient hypoxia, cold temperatures, and food scarcity. They have evolved novel hemoglobin isoforms with increased O 2 binding affinity to surmount partially the low ambient O 2 availability (7,27,64); however, these isoforms are not always expressed and are insufficient to support the aerobic demands of deer mice fully, necessitating other strategies to increase O 2 uptake and delivery. Hammond et al (18) reported that deer mice that were raised and tested at LA exhibit higher aerobic capacity and basal metabolic rate than those that were either raised or acclimated as adults and tested at HA.…”
Section: Discussionmentioning
confidence: 99%
“…The heme groups of mouse met Hb and their environmental residues are shown as 2F o À F c electron-density maps in Fig. 4 (Inoguchi et al, 2013(Inoguchi et al, , 2017Pairet & Jaenicke, 2010;Shaanan, 1983;Vá squez et al, 1998;Fermi et al, 1984;Biswal & Vijayan, 2001). From the heme geometry, the distances between Fe and Geometry of the heme groups and their environment in mouse, human, DMouse and GPig Hbs.…”
Section: Heme Analysismentioning
confidence: 99%
“…Molecular and genetic approaches have provided valuable insights into the biochemical mechanisms underlying this evolved change in Hb function. The specific amino acid replacements that are responsible for evolved changes in Hb-O2 affinity have been identified (Storz et al, 2012;Storz et al, 2010;Storz et al, 2009) and crystallographic studies have revealed the biophysical mechanisms by which mutations exert their effects (Inoguchi et al, 2017;Inoguchi et al, 2013;Natarajan et al, 2015). Protein engineering has shown that these modifications lead to increases in Hb-O2 affinity for isolated protein in vitro, without affecting the Bohr effect (Jensen et al, 2016;Natarajan et al, 2013).…”
Section: Determinants Of Adaptive Variation In Aerobic Capacity Acros...mentioning
confidence: 99%